Chromosome-level genome assembly of Eimeria tenella at the single-oocyst level - Kaihui Zhang; Yudong Cai; Yuancai Chen; Yin Fu; Ziqi Zhu; Jianying Huang; Huikai Qin; Qimeng Yang; Xinmei Li; Yayun Wu; Xun Suo; Yu Jiang; et al. (BMC Genomics)
Abstract Background Eimeria are obligate protozoan parasites, and more than 1,500 species have been reported. However, Eimeria genomes lag behind many other eukaryotes since obtaining many oocysts is difficult due to a lack of sustainable in vitro culture, highly repetitive sequences, and mixed species infections. To address this challenge, we used whole-genome amplification of a single oocyst followed by long-read sequencing and obtained a chromosome-level genome of Eimeria tenella. Results The assembled genome was 52.13 Mb long, encompassing 15 chromosomes and 46.94% repeat sequences. In total, 7,296 protein-coding genes were predicted, exhibiting high completeness, with 92.00% single-copy BUSCO genes. To the best of our knowledge, this is the first chromosome-level assembly of E. tenella using a combination of single-oocyst whole-genome amplification and long-read sequencing. Comparative genomic and transcriptome analyses confirmed evolutionary relationship and supported estimates of divergence time of apicomplexan parasites and identified AP2 and Myb gene families that may play indispensable roles in regulating the growth and development of E. tenella. Conclusion This high-quality genome assembly and the established sequencing strategy provide valuable community resources for comparative genomic and evolutionary analyses of the Eimeria clade. Additionally, our study also provides a valuable resource for exploring the roles of AP2 and Myb transcription factor genes in regulating the development of Eimeria parasites.